Similar culture, different tourist behavior?: results from cross-cultural research on the tourist behavior of college students - Závodný Pospíšil, Jan; Xara-Brasil, Duarte; Závodná, Lucie Sára (My University, 2023)
The paper aims to enhance the understanding of the behavior of international tourists; this study (1) determines if cultural differences exist between Portuguese, Brazilian, Mexican, and Colombian college students; (2) if these students differ in their travel preferences; (3) examines if horizontal/vertical individualism correlates with the students' travel preferences. A psychographic approach based on value orientations was used to understand the relationship between travel preferences and the students' cultural tendencies to horizontal and vertical individualism and collectivism. The results showed that Portuguese, Brazilian, Mexican, and Colombian students have similar cultural dimensions at the societal level but differ at the individual cultural level. Although their tourist preferences differ fundamentally, no significant evidence of a relationship between the cultural tendencies and the tourist behavior of the measured samples of students has been found. The paper uses a combination of known and proven methods to obtain and process primary data. The findings provide new insights that can enhance the current knowledge of tourism research and marketing. The paper's results imply the need to revise the current understanding of differences in cultural tendencies on tourist behavior. However, it is necessary to consider some limitations arising from the sample selection and cultural tendencies measurement methods.
Keywords: Tourist Behavior; Cultural Differences; Portugal; Brazil; Mexico; Colombia